Expression of growth-factor receptors in normal and regenerating human periodontal cells - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
Growth factors are biologically active mediators that bind to specific receptors on target cells and regulate genes involved in cell growth, wound healing and regeneration. The expression of these receptors is thus of fundamental importance for the response of the cells to the factors. The aim here was to examine, using immunohistochemistry and flow cytometry, the expression of growth factor receptors in normal gingiva, periodontal ligament and in cells derived from these tissues, and also in regenerated tissues following guided tissue regeneration (GTR). By immunocytochemistry platelet-derived growth factor receptor-alpha (PDGF-R alpha) was not detected in any of the tissues, whereas the PDGF-R beta and transforming growth factor-beta receptor types I and II (TGF-beta RI, RII) appeared to be upregulated in regenerated tissues compared with gingival and periodontal ligament tissues. Epidermal growth factor receptor (EGF-R) was also notably elevated in the regenerated tissue and was strongly expressed in the gingival epithelium but not in the periodontal ligament. Neither were fibroblast growth factor receptor-I (FGF-RI) or insulin-like growth factor receptor (IGF-R) detected in the periodontal ligament, nor in the gingiva, but they sometimes stained weakly in the regenerated tissues. Flow cytometry (FCM) showed that all the cells derived from the normal gingiva and the periodontal ligament expressed the PDGF-R beta, whereas the TGF-beta RI and RII, FGF-RI and IGF-R were detected in only a proportion of the total cells. In contrast, none of the cells expressed the PDGF-R alpha or the EGF-R. These observations show that the growth factor receptors are differentially expressed by the periodontal tissues and cells and suggest that the corresponding factors may also be differentially involved in periodontal wound healing and regeneration. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: growth factors; receptors; periodontal cells; LIGAMENT FIBROBLASTIC CELLS; FACTOR-I; FLOW-CYTOMETRY; HUMAN GINGIVAL; DNA-SYNTHESIS; FACTOR-BETA; PDGF-ALPHA; TGF-BETA; BINDING; RAT